SOFT POWER PARADIGM OF INDONESIA’S DEFENSE - Arthur Josias Simon Runturambe; Yudha Fernando (The Republic of Indonesia Defense University, 2022)
The proposed strategic budget of US 104,247 billion submitted by Indonesia’s Ministry of Defense in mid-2021 has created a debate about Indonesia's Quo Vadis defense spending. Some questions need to be answered to provide insight into the process of selecting the best method for Indonesia's defense. Increasing national defense capabilities should refer to the global dynamics to accommodate Indonesia's national interests. This research uses document study, Focus Group Discussion (FGD), field observations for data collection, PEST analysis (Political, Economy, Social, and Technology), as well as SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), and ends with interactive analysis to obtain inductive conclusions. The purpose of this study is to see how Indonesia's weaknesses and strengths, both hard power and soft power, thus proceed to interactive analysis. The results show that the soft power method is considered the most appropriate to the current global and strategic conditions. Increasing the capability of the defense equipment only without prioritizing aspects of the soft power approach has the potential to make Indonesia included in the mapping of major power state threats. The soft power approach must be put forward but also mutually enable hard power capabilities. The mutualism of those aspects is considered effective to gain Indonesia’s defense strength.